Ethnic imaginary and humanist utopia in the work Trocitos de carbón of Carlos Gagini - Herrera Valenciano, Minor (2018)
This paper addresses the text Trocitos de carbón of Carlos Gagini from two perspectives: on the one hand, as a text that shows the existing ethno-cultural imaginary about the "African descent" during the nineteenth century in Costa Rica and, moreover, as text that facilitates human models and initial experiences, from which the reader acquires conceptual tools to learn to interact with different cultural and contextual products in which it shall live.